Atmospheric forcing and ocean preconditioning for dense shelf water cascading in the northwestern Mediterranean - Helena Fos; Anna Sanchez-Vidal; Jesús Peña-Izquierdo; Víctor Estella-Pérez; Cristian Florindo-Lopez; Marta Arjona-Camas; Antoni Calafat; Xavier Durrieu de Madron; Maxime Lagarde; David Amblas (Climate Dynamics, 2026)
Dense shelf water cascading (DSWC) in the northwestern Mediterranean Sea occurs due to the densification and overflow of shelf water in winter. This process ventilates the deep basin with waters that can be denser than those generated by open-ocean convection. Between 1987 and 2021 (i.e., 35 winter periods), shelf water reached depths greater than 1000 m on only 9 occasions, and open questions remain regarding the triggering factors and inhibitors for these deep DSWC events. Combining atmospheric and ocean reanalysis data, we found that, at interannual scales, the East Atlantic (EA) mode of climate variability is more strongly associated with the thermal components of the atmospheric forcing: air temperature, wind, and sea surface temperature, contributing to a strong connection between the negative phase of EA, and an increased heat loss and buoyancy loss. At shorter synoptic to subseasonal time scales, the dense shelf water formation in winter is linked to the local northerly winds and cold air outbursts. As important as the thermal atmospheric forcing, the evaporation-precipitation balance and river runoff play a key role in facilitating or preventing dense shelf water formation and cascading. Besides, the temperature of surface shelf water at the beginning of winter can be critical. In the years after an intense DSWC event, the favorable preconditioning by advected dense water and reduced intermediate stratification enhances deep cascading. These insights are meaningful for how the atmospheric and oceanic signals from a changing climate propagate into the deep Mediterranean Sea, which ultimately could affect the thermohaline circulation.